Financial Inclusion and Promotion Drive Halal Micro Business Interest in Islamic Financing: Inklusi Keuangan dan Upaya Promosi Meningkatkan Minat Usaha Mikro Halal terhadap Pembiayaan Islam - Dita Aprilia Ningsih; Riyan Pradesyah (Academia Open, 2025)
General Background: Islamic financial institutions are instrumental in offering Sharia-compliant services that foster equitable economic growth. Specific Background: Among their key focus areas is empowering Usaha Mikro, Kecil, dan Menengah (UMKM), particularly halal-certified enterprises, through accessible financing.Knowledge Gap: However, limited research explores how financial inclusion and promotional strategies influence halal UMKM actors' preferences for Islamic bank financing, especially at the regional level. Aims: This study investigates the impact of financial inclusion and promotion on the interest of halal UMKM actors in Aek Songsongan District in utilizing Islamic financing. Results: Based on a quantitative analysis of 174 respondents using multiple linear regression, findings reveal that both financial inclusion and promotion significantly and positively affect interest in Islamic financing, both simultaneously and partially. Novelty: The study uniquely integrates financial behavior and promotional outreach variables in a rural halal UMKM context, offering empirical evidence from an under-researched district. Implications: Results highlight the need for Islamic banks to intensify inclusive financial strategies and targeted promotional efforts to enhance engagement among halal micro-entrepreneurs. Highlights: Highlights the role of Islamic banks in supporting halal UMKM. Shows how financial inclusion and promotion influence financing interest. Offers insights for improving Islamic financial outreach strategies. Keywords: Financial Inclusion, Islamic Financing, Halal UMKM, Promotion Strategy, Islamic Banks